Axoplasmic reticulum Ca2+ release causes secondary degeneration of spinal axons. Issue 2 (18th February 2014) - Stirling, David P.; Cummins, Karen; Wayne Chen, S. R.; Stys, Peter
<x xml:space="preserve">Abstract</x> Objective Transected axons of the central nervous system fail to regenerate and instead die back away from the lesion site, resulting in permanent disability. Although both intrinsic (eg, microtubule instability, calpain activation) and extrinsic (ie, macrophages) processes are implicated in axonal dieback, the underlying mechanisms remain uncertain. Furthermore, the precise mechanisms that cause delayed "bystander" loss of spinal axons, that is, ones that were not directly damaged by the initial insult, but succumbed to secondary degeneration, remain unclear. Our goal was to evaluate the role of intra‐axonal Ca2+ stores in secondary axonal degeneration following spinal cord injury. Methods We developed a 2‐photon laser‐induced spinal cord injury model to follow morphological and Ca2+ changes in live myelinated spinal axons acutely following injury. Results Transected axons "died back" within swollen myelin or underwent synchronous pan‐fragmentation associated with robust Ca2+ increases. Spared fibers underwent delayed secondary bystander degeneration. Reducing Ca2+ release from axonal stores mediated by ryanodine and inositol triphosphate receptors significantly decreased axonal dieback and bystander injury. Conversely, a gain‐of‐function ryanodine receptor 2 mutant or pharmacological treatments that promote axonal store Ca2+ release worsened these events. Interpretation Ca2+ release from intra‐axonal Ca2+ stores, distributed along the length of the axon, contributes significantly to secondary degeneration of axons. This refocuses our approach to protecting spinal white matter tracts, where emphasis has been placed on limiting Ca2+ entry from the extracellular space across cell membranes, and emphasizes that modulation of axonal Ca2+ stores may be a key pharmacotherapeutic goal in spinal cord injury. Ann Neurol 2014;75:220–229